Gamification des sciences participatives et transition numérique des espaces de montagne : le cas du Réseau gypaète Mercantour - Alain Schoeny (Revue de Géographie Alpine)
Participatory science is an alternative to certain mountain practices. At local, it rests on collaborations between scientists and citizens. In France, the Mercantour National Park, a unique territory, is an interesting case for study. Located in the Provence-Alpes-Côte d'Azur region, it has, since 1993, been the setting for a program of reintroduction of bearded vultures. Thus, the Park, with over 500 volunteers, has organized itself to follow its evolution. Digital technologies play an important part in this, particularly in the collection, transmission and exchange of data, and various game mechanisms contribute to the gamification of bearded vulture monitoring in the Mercantour. This article then specifies its outlines so as to help better understand its principles, which have more to do with play-oriented attitudes towards non-recreational objects than with a conquest of recreational objects. A survey, interviews and IT monitoring were thus conducted to explain what can today be described as gamification of participatory science, which the digital transition has activated.